O conto da aia e Os testamentos: Da repressão ao legado dos relatos de Offred e Tia Lydia - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
The Handmaid’s Tale (1985) and The Testaments (2019) depict a totalitarian regime known as the Republic of Gilead. This regime aims to curtail the civil, political and sexual rights of women. Offred and Aunt Lydia are some of the dystopian heroines in these novels. Hierarchically, they are in distinct social positions. Offred, as a Handmaid, has her body objectified and instrumentalized for reproductive purposes. Aunt Lydia, in turn, is responsible for training the Handmaids and the Postulants. Despite having different roles and varying degrees of importance and influence, both Offred and Aunt Lydia are victims of the regime. They are deprived of freedom and have their bodies constrained to dress and act according to their assigned social roles. However, they use their memories and narratives as forms of resistance and affirmation of their individuality. Raffaella Baccolini (2022) considers that a key characteristic of the critical dystopia is the depict of utopian enclaves, such as resistance movements – individual or collective. These movements can constitute a counter-narrative of resistance by dystopian heroes and heroines against the hegemonic narrative, often represented by the totalitarian state. Therefore, the dissertation aims to analyze both the control apparatus and resistance movements of the dystopian heroines Offred and Aunt Lydia in order to identify the various possibilities of domination and/or affirmation of their individuality. By contrasting their stories, I also aim to gain a better understanding of the social roles they play and the functioning of the dystopian social structure. The analysis of Margaret Atwood's feminist critical dystopias, The Handmaid's Tale and The Testaments, stemmed from my desire to better understand the dynamics of power established, especially in relation to gender inequalities and the silencing imposed on women. The research is supported by a theorical framework concerning the relation between Literature and utopia/dystopia, as well as Mikhail Bakhtin’s (2002) concept of dialogism and centripetal and centrifugal forces at play in discourse and Michel Foucault’s (2011) concept of the apparatus.
Keywords: Offred; Tia Lydia; Distopia crítica; Offred; Aunt Lydia; Critical dystopia; CNPQ::LINGUISTICA, LETRAS E ARTES